Psychological wellbeing of student-athletes: a comparative study between European and American athletes - Keriven, Hugo; Sánchez-Sierra, Alberto; de-la-Plaza-San-Frutos, Marta; García-Pérez-de-Sevilla, Guillermo; Clemente-Suarez, Vicente; Garcia-Laredo, Eduardo; Saenz-Bravo, Marisa; B A Owoeye, Oluwatoyosi; Miñambres-Martín, Diego; Domínguez-Balmaseda, Diego (Frontiers in Psychology, 2026)
Sports-related injuries occur at rates ranging from 0.5 to 34 per 1,000 practice hours and are a leading cause of early retirement, with psychosocial factors influencing recovery. Injury prevention remains a priority because of its financial and performance impacts on teams. Psychological factors, such as attention disturbances, negative life events, and arousal levels, can impact an athlete's risk of injury, although psychological interventions are rarely used in sports. Fear of failure, a major stress factor, negatively affects athletes' motivation and self-perception. Stress and recovery responses vary across cultures, with European and American athletes employing different strategies. Understanding these cultural differences could help tailor interventions to improve performance and wellbeing. This study compared stress and recovery parameters between American and European student-athletes. This observational pilot clinical trial aimed to assess stress and quality of life among young athletes from two universities: Universidad Europea de Madrid UEM and Saint Louis University (SLU), in pre-season conditions. Participants recruited from their respective soccer teams completed a one-time questionnaire to assess social- and sports-related stress. The study followed ethical guidelines and the questionnaires included tools such as the POMS, RESTQ-52, and the Groningen Sleep Questionnaire. This study found significant differences between the groups across various stress categories, including general, emotional, social, and sports-specific stress, as well as fatigue and disturbed breaks, with p-values ranging from 0.005 to 0.035. The effect sizes for these differences were moderate, with values ranging from r = -0.321 to r = -0.429. Overall, significant differences between the groups were observed, with moderate effect sizes for both general and Overall Stress Scores (r = -0.397 and r = -0.414, respectively). This study highlights significant cultural differences in stress, recovery, sleep quality, and mood between student-athletes at UEM and SLU. These findings emphasize the need for tailored psychological interventions and recovery strategies that address athletes' unique stressors and cultural environments and improve their performance and wellbeing.
Keywords: injury prevention; stress; recovery; athletes; wellbeing; psychosocial factors